Analytical and numerical study Of Slope Stability Supported by soil nailing، Case study: Qarfees slope - مهنا, مهند (Latakia University Journal -Engineering Sciences Series, 2023)
This research aims to evaluate the stability of rocky slopes exposed to weathering factors and engineering activities, in addition to proposing an appropriate supporting by using soil nails technique. For this purpose, the stability of the damaged rocky slope next to Qarfees Reservoir was analyzed as a case study for practical application. The research was carried out in three stages: In the first stage, field investigations were carried out executing geophysical measurements and rotary boreholes, in order to determine the physical and mechanical properties of the rock layers at Qarfees site. In the second stage: the stability of the rock slope was assessed based on the field data. Moreover, a numerical model using Geostru-slope program was done to calculate the critical slip surfaces and the corresponding safety factors. As for the third stage, it corresponds to an analytical and numerical study of the efficiency of soil nailing in supporting the rocky slope, in addition to the evaluation of the governing parameters affecting stability. The numerical study showed the efficiency of soil nailing in increasing the slope stability, whereas the stability of the slope depends significantly on the nail length that must penetrate the slip surface to reach the stable area, the general safety factor increases by increasing the lengths of the nails until reaching a length of 0.6 of the slope height. It was also found that the ideal angle of nail inclination was about 20° from the horizon. In addition to the above, the study concluded that the safety factor decreased when the horizontal spacing between nails increased, as it was noted that the safety factor decreased by 60% when the horizontal spacing increased by three times.